2022
DOI: 10.3390/ijms23116262
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigations on the Metabolic and Transcriptomic Regulation of Lactate in the Human Colon Epithelial Cells

Abstract: Lactate, primarily produced by the gut microbiota, performs as a necessary “information transmission carrier” between the gut and the microbiota. To investigate the role of lactate in the gut epithelium cell–microbiota interactions as a metabolic signal, we performed a combinatory, global, and unbiased analysis of metabolomic and transcriptional profiling in human colon epithelial cells (Caco-2), using a lactate treatment at the physiological concentration (8 mM). The data demonstrated that most of the genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 97 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Our previous RNA-seq data demonstrated that lactate, a microbial metabolite like the SCFAs, significantly upregulated ROS metabolism and disturbed mitochondrial function by downregulating the electron transport chain and oxidative phosphorylation in Caco-2 cells [35] , which endogenously generated ROS in the mitochondria [4] . Consistently, ROS-mediated fluorescence was significantly promoted by increasing the concentrations of SCFAs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous RNA-seq data demonstrated that lactate, a microbial metabolite like the SCFAs, significantly upregulated ROS metabolism and disturbed mitochondrial function by downregulating the electron transport chain and oxidative phosphorylation in Caco-2 cells [35] , which endogenously generated ROS in the mitochondria [4] . Consistently, ROS-mediated fluorescence was significantly promoted by increasing the concentrations of SCFAs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dysfunctional mitochondria induce transcriptomic and metabolic disturbances [35] . Our results showed that SCFAs led to mitochondrial activity dysfunctions, such as the electron transport chain and oxidative phosphorylation and alterations in the expression of several genes related to mitochondrial function, such as decreased MT-NDs , MT-CO1 , and MT-ATP6 and increased PIP5KL1 , UCP1 , and C15ORF48 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…44 In turn, the highest lactate production, was found in the samples treated with L. rhamnosus which coincides with a previous study of our group, in which L. rhamnosus supplementation reflected the increase in lactate after 20 days of supplementation on colonic microbiota of children with CF. 18 This finding is relevant since it is known that lactate is a beneficial metabolite that exerts a positive role on the body such as regulating the biological processes of intestinal function, produces an indirect inhibition of the growth of pathogenic bacteria, and the genus Lactobacillus is related to its biosynthesis to produce propionate, butyrate, or acetate 45,46 In the case of the production of acetic acid and propionic acid, the combination of pectin with L. rhamnosus allowed for a twofold increase of the amount of these metabolites with respect to the initial content. Besides, SCFAs and the genus Bacteroides showed a positive correlation, suggesting a symbiotic effect of pectin-L. rhamnosus: the changes induced in the microbiota, such as the increase in Bacteroides, seem to modify the metabolism of pectin, resulting in higher short-chain fatty acids production.…”
Section: Discussionmentioning
confidence: 99%
“…44 In turn, the highest lactate production, was found in the samples treated with L. rhamnosus which coincides with a previous study of our group, in which L. rhamnosus supplementation reflected the increase in lactate after 20 days of supplementation on colonic microbiota of children with CF. 18 This finding is relevant since it is known that lactate is a beneficial metabolite that exerts a positive role on the body such as regulating the biological processes of intestinal function, produces an indirect inhibition of the growth of pathogenic bacteria, and the genus Lactobacillus is related to its biosynthesis to produce propionate, butyrate, or acetate 45,46…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated lactate's ability to modulate the binding of H3K27ac to promoter regions and cis -regulatory elements, influencing chromatin accessibility [ 64 ]. Similarly, incubating cells with lactate has been shown to induce a less compact chromatin structure, creating a transcriptionally permissive chromatin conformational state that facilitates DNA transcriptional machinery [ 65 , 66 ]. In our investigation, we observed that lactate-mediated chromatin accessibility was, at least partly, driven by increased binding of JUNB to the chromatin.…”
Section: Discussionmentioning
confidence: 99%